DIGITAL PEDAGOGY IN PRIMARY EDUCATION: DEVELOPING SIPEJAR MICROLEARNING TO CULTIVATE CRITICAL THINKING SKILLS - Utama, Candra; Mashfufah, Aynin; Thohir, M. Anas (Universitas Labuhanbatu, 2024)
The digital revolution has reshaped the global educational landscape, necessitating the integration of technology into learning processes, particularly in primary education. Critical thinking skills have emerged as essential 21st-century competencies required to navigate the information era. Traditional teaching methods often fall short in facilitating the optimal development of these skills. Digital pedagogical approaches such as microlearning offer innovative solutions, enabling students to access information in focused, interactive, and flexible ways.Purpose - This study aims to develop SIPEJAR-based microlearning modules and evaluate their effectiveness in enhancing critical thinking skills among Primary School Teacher Education (PGSD) students.Methodology - Employing the ADDIE development method (Analysis, Design, Development, Implementation, Evaluation), the study included expert validation of the module content and its implementation involving 76 students divided into experimental and control groups.Findings - The results revealed that integrating SIPEJAR-based microlearning significantly improved critical thinking skills in the experimental group, with a statistically significant difference in post-test scores compared to the control group (p < 0.05). Key success factors included modular design, interactive multimedia, and flexible access.Significance - This research offers significant benefits to educators, particularly prospective primary school teachers, equipping them with digital pedagogical strategies to prepare students for global challenges. Additionally, this approach serves as a reference for digital learning innovations at other educational levels. The study highlights technology's role as a catalyst for 21st-century learning, fostering interactive, relevant, and adaptive learning environments.